Dismemberment at Windmill Point: Violence, Manliness, and The Irish in Upper Canada - McGaughey, Jane (Ontario History, 2018)
Drawing on personal letters, published memoirs, and court martial records, this article investigates the gendered and ethnic implications of the Battle of the Windmill in November 1838. While this invasion of Upper Canada by the Hunter Patriots has often been seen as the final chapter of the 1837 Canadian Rebellions, it was also an episode imbued with Irish fraternal societies, Irish politics, notions of Irish manliness, and the attempts of Irish settlers to earn their place within “respectable” Upper Canadian society. The scandalous castration of an Irish officer and the mistreatment of dead soldiers’ bodies stood in direct contrast to the value each force placed on heroic martial manliness. Despite the relatively small size of the battlefield, the legacy of the battle itself significantly impacted how Irish settlers were treated in Upper Canadian society at the end of the 1830s.